2023
DOI: 10.1186/s13046-023-02686-1
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine conquers temozolomide chemoradiotherapy resistance to achieve immune cure in refractory glioblastoma via boosting oxidative stress-inflamation-CD8+-T cell immunity

Abstract: Background The failure of novel therapies effective in preclinical animal models largely reflects the fact that current models do not really mimic the pathological/therapeutic features of glioblastoma (GBM), in which the most effective temozolomide chemoradiotherapy (RT/TMZ) regimen can only slightly extend survival. How to improve RT/TMZ efficacy remains a major challenge in clinic. Methods Syngeneic G422TN-GBM model mice were subject to RT/TMZ, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Analysis of the DEGs through the KEGG pathway database revealed that they were primarily enriched in pathways including "complement and coagulation cascades", the "PI3K-Akt pathway signaling pathway", "Staphylococcus aureus infection", "Glutathione metabolism" and "Primary bile acid biosynthesis". Most of these pathways are associated with the immune system and infectious diseases [60][61][62][63]. This study showed that LPS upregulated the expression of differentially expressed genes involved in complement and coagulation cascade reactions, including CFD, F2RL2, CFB, C4BPA, F7, C4BPB, CFH, C3 and PROS1, and downregulated KLKB1 levels.…”
Section: Discussionmentioning
confidence: 67%
“…Analysis of the DEGs through the KEGG pathway database revealed that they were primarily enriched in pathways including "complement and coagulation cascades", the "PI3K-Akt pathway signaling pathway", "Staphylococcus aureus infection", "Glutathione metabolism" and "Primary bile acid biosynthesis". Most of these pathways are associated with the immune system and infectious diseases [60][61][62][63]. This study showed that LPS upregulated the expression of differentially expressed genes involved in complement and coagulation cascade reactions, including CFD, F2RL2, CFB, C4BPA, F7, C4BPB, CFH, C3 and PROS1, and downregulated KLKB1 levels.…”
Section: Discussionmentioning
confidence: 67%
“…TMZ (Sigma, St Louis, MO, USA) and EVO (TH-302; Threshold Pharmaceuticals, South San Francisco, CA, USA) were prepared for use in treating the cell lines or mice by dissolving and diluting them in either 0.05% dimethyl sulfoxide or PBS, in accordance with the manufacturer's protocols and previous reports [14,15,19].…”
Section: Reagentsmentioning
confidence: 99%
“…We did come across a curious case where a mouse glioma cell line cultured as tumors in mice was evaluated for gene expression by both RT-PCR and FPKM [91]. The FPKM metric implied GPX2 expression amounted to ~0.003% of the total antioxidant enzyme gene profile (0.75/26,000-42,000 total FPKM) across four sets of experimental conditions, with only small variation (range, 0-4 FPKM; note that a positive signal was reported for none of the samples in one set, one of three samples in two sets, and two of three samples in the last set).…”
Section: Building Antioxidant Enzyme Expression Profiles In Tumor-der...mentioning
confidence: 99%